Uji Aktivitas Antioksidan Ekstrak Etanol Herba Sirih Cina (Peperomia pellucida L.) dengan Metode DPPH - Jecika Stefany Br Tumanggor; Razoki Razoki; Muhammad Yunus; Daimah Wirdatus Sanaun Harahap (Pusat Riset dan Inovasi Nasional, 2025)
Free radicals are reactive compounds that can cause damage to cells, enzymes, lipids, and even DNA, thus triggering various degenerative diseases. Antioxidants neutralize free radicals and prevent oxidative damage. Chinese betel herb (Peperomia pellucida L.) is known to contain phenol and flavonoid secondary metabolite compounds that act as natural antioxidants. This study aims to test the antioxidant activity of ethanol extract of Chinese betel herb with DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Extraction was done by maceration method using 80% ethanol solvent. Antioxidant activity was tested by reacting the extract against DPPH solution and measuring the absorbance using UV-Vis spectrophotometry. The results showed an IC₅₀ value of 32.97 ppm, which is classified as very strong antioxidant activity. These results indicate that ethanol extract of Chinese betel herb has great potential as a source of natural antioxidants.